Phytochemical Composition, Antioxidant Activity, and Enzyme Inhibitory Activities (α-Glucosidase, Xanthine Oxidase, and Acetylcholinesterase) of Musella lasiocarpa - Rurui Li; Yuerong Ru; Zhenxing Wang; Xiahong He; Kin-Weng Kong; Tingting Zheng; Xuechun Zhang (Molecules, 2021)
In this study, we aimed to investigate the chemical components and biological activities of Musella lasiocarpa, a special flower that is edible and has functional properties. The crude methanol extract and its four fractions (petroleum ether, ethyl acetate, n-butanol, and aqueous fractions) were tested for their total antioxidant capacity, followed by their α-glucosidase, acetylcholinesterase, and xanthine oxidase inhibitory activities. Among the samples, the highest total phenolic and total flavonoid contents were found in the ethyl acetate (EtOAc) fraction (224.99 mg GAE/g DE) and crude methanol extract (187.81 mg QE/g DE), respectively. The EtOAc fraction of Musella lasiocarpa exhibited the strongest DPPH· scavenging ability, ABTS·+ scavenging ability, and α-glucosidase inhibitory activity with the IC50 values of 22.17, 12.10, and 125.66 μg/mL, respectively. The EtOAc fraction also showed the strongest ferric reducing antioxidant power (1513.89 mg FeSO4/g DE) and oxygen radical absorbance capacity ability (524.11 mg Trolox/g DE), which were higher than those of the control BHT. In contrast, the aqueous fraction demonstrated the highest acetylcholinesterase inhibitory activity (IC50 = 10.11 μg/mL), and the best xanthine oxidase inhibitory ability (IC50 = 5.23 μg/mL) was observed from the crude methanol extract as compared with allopurinol (24.85 μg/mL). The HPLC-MS/MS and GC-MS analyses further revealed an impressive arsenal of compounds, including phenolic acids, fatty acids, esters, terpenoids, and flavonoids, in the most biologically active EtOAc fraction. Taken together, this is the first report indicating the potential of Musella lasiocarpa as an excellent natural source of antioxidants with possible therapeutic, nutraceutical, and functional food applications.